Demographic and clinical features of rosacea in North Jordan: a 10-year university hospital retrospective study - Diala Alshiyab; Saleh A. Ba-shammakh; Alaa Bani Bakr; Mohammad Abu-Hussein; Abdulqudos Al-Fakih; Sarah Alawneh; Leen Alhuneafat; Leen Heis; Firas Al-qarqaz (Annals of Medicine)
Background/Objectives This study aims to investigate the demographic and clinical characteristics of rosacea within the North Jordan population, focusing on Fitzpatrick skin types III and IV. The intent is to address gaps in dermatological research concerning ethnic and racial variations in rosacea’s presentation and impact.Methods We conducted a retrospective cohort analysis at the dermatology department of King Abdullah University Hospital, North Jordan, reviewing medical records of patients diagnosed with rosacea from January 2013 to December 2023. Data collection focused on demographics, rosacea subtypes and environmental factors exacerbating the condition. Statistical analysis utilized Jamovi and GraphPad Prism software.Results The study included 610 patients, revealing a rosacea prevalence of 1.5% within the hospital’s catchment area. Most patients were female (84.4%), with a median age of 44. The majority had Fitzpatrick skin types III and IV. The erythematotelangiectatic subtype was most common (73.6%), followed by papulopustular (23.4%) and phymatous (3%). Environmental triggers like sun exposure and temperature changes were nearly universally reported as exacerbating factors.Conclusions Rosacea shows significant gender disparities and is influenced by environmental factors. The study underscores the need for targeted research and treatment strategies that consider ethnic and racial variations, along with gender-specific presentations of the disease.